Educational innovations during the war: the role of the head of a higher education institution in modifying the system - Filipenko, Nataliia; Ivanović, Aleksandar (Archives of Criminology and Forensic Sciences, 2025)
This article provides a comprehensive analysis of the role of higher education institution leaders in driving educational innovations during wartime, emphasizing their strategic importance in maintaining academic stability and fostering adaptation to crisis conditions. The study explores the multifaceted challenges faced by the educational system, including the large-scale destruction of infrastructure, disruptions in the learning environment, the urgent need for digital transformation, and the psychological toll on students and faculty. Additionally, it examines the critical role of international collaboration in sustaining academic activities and ensuring access to global educational resources. Recognizing the leadership imperative in times of crisis, the article delves into innovative management approaches that facilitate the transformation of higher education institutions to align with evolving societal needs. Key areas of innovation include the implementation of digital administration systems to streamline operational efficiency, the integration of interactive learning methodologies to enhance student engagement, and the gamification of academic programs to foster motivation and knowledge retention. Furthermore, strategic planning emerges as a fundamental tool in crisis management, enabling leaders to develop adaptive frameworks that support institutional resilience. The discussion also underscores the necessity of expanding international cooperation, leveraging partnerships with global academic networks to secure funding, share best practices, and facilitate cross-border educational exchange programs. A focal point of the study is the evolving role of higher education leaders as agents of change, driving the modernization of academic policies, curricula, and technological infrastructures to meet contemporary educational demands. Through the synthesis of innovative strategies and leadership-driven initiatives, the article presents a roadmap for the progressive transformation of the higher education sector, ensuring its sustainability and long-term relevance amid wartime disruptions.